Effects of Phloroglucinol on In Vitro Methanogenesis, Rumen Fermentation, and Microbial Population Density - Sarwono, K. A.; Kondo, M.; Ban-Tokuda, T.; Jayanegara, A.; Matsui, H. (Tropical Animal Science Journal, 2019)
This study investigated the effect of phloroglucinol (1,3,5-trihydroxybenzene) supplementation alone on methane production, rumen fermentation profiles, and microbial population structure of mixed in vitro cultures. Treatments included a control group containing a substrate with no supplement, and substrates supplemented with 2, 4, 6, 8, or 10 mmol/L of phloroglucinol. The results revealed that phloroglucinol was able to decrease methane production in a dose-dependent manner. The highest decrease was observed with 8 and 10 mmol/L supplementations. The relative quantity of methanogen was not affected by phloroglucinol, whereas genus Coprococcus was increased with increasing concentrations of phloroglucinol (p